Perilaku Asertif dan Psychological Well Being: Bagaimana Pengaruhnya terhadap Siswa? - Fauziah, Mufied; Purwadi, Purwadi; Arikunto, Suharsimi; Setyowati, Aprilia; Nabila, Hurin; Herdiansyah, Diki; Nurhidayat, Ardi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Psychological well-being is another concept that illustrates essential aspects of human functioning, such as positive relationships, competence, and meaning and purpose in life. This study aims to examine the relationship between psychological well-being and assertive behavior. The research uses a quantitative approach with a survey method to describe psychological well-being. The subjects of this study are 137 students from SMP Negeri 15 Yogyakarta, selected using simple random sampling. Data analysis techniques used SPSS to perform simple regression analysis. The results show a significant influence of assertive behavior on the students' psychological well-being. The impact of assertive behavior on psychological well-being is 37.7%, while the remaining 62.3% is influenced by other variables not studied. This research recommends the inclusion of assertive behavior to enhance psychological well-being when providing guidance and counseling services to students.